FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN MOBILE BANKING(STUDI KASUS MAHASISWA UNIVERSITAS SURABAYA) - Ismi Fatmala Sarofah (Perpustakaan Universitas Surabaya, 2018)
Mobile Banking is a system service from a financial institutionsuch as a Bank to do number of financial transactions which can be accesseddirectly by the customer through mobile devices such ascell phones. This research aims to know the influence of perceptions of ease, security, and benefits against the interest in using mobile banking. This research is descriptive quantitative research with survey method. The population in this research is the studentsof the University of Surabayawho use mobile banking. Instruments test, the classical assumptions test, and data analysis test in this research using SPSS 20.00. From the result of the research note that the ease of perception of positive but not significant effect against the interest in using mobile banking. While the perception of security and the benefits of a positive and significant effect against the interest in using mobile banking.